Estudo químico e avaliação da atividade antimicrobiana dos óleos essenciais extraidos das especies Pimenta dioica (Myrtaceae) e Chenopodium ambrosioides (Amaranthaceae) - Phanord, Clerlune [UNIFESP] (2016)
Currently infectious diseases remain one of the most serious public health problems and have caused many deaths. According to OMS, infectious diseases caused 14.7 million deaths in 2001, or 26% of total world mortality. Since the discovery of penicillin by Alexander Fleming in 1928, many antibiotics are available in pharmacies, but despite the existence of these antibiotics, infectious diseases, instead of being completely eradicated are reappearing and also new infectious diseases have emerged. The causes of this problem are diverse: there are few specific antibiotics available, the treatment is very expensive, and the most disturbing: the microorganisms are increasingly resistant to antibiotics. Therefore, as a contribution to the discovery of new antibiotics, this study aimed to find new substances that might be prototypes of antimicrobial drugs, or at least an effective and low cost to fight these pathogens. Thus, the chemical study was proposed of the essential oils of the species Pimenta dioica (Myrtaceae) and Chenopodium ambrosioides (Amaranthaceae), and the evaluation of antimicrobial activity against various strains of bacteria and yeast. The majority of essential oil compounds of P. dioica were phenylpropanoids eugenol and chavicol beyond monoterpene myrcene, whereas for C. ambrosioides were monoterpenes: ascaridol and terpinene. Regarding the antimicrobial activity, the tested strains showed sensitivity to the essential oil of P. dioica and the isolated compound eugenol, except for Pseudomonas aeruginosa. The MIC90 for both ranged from 0.25 mg/mL for E. faecalis and 1 mg/mL for all tested bacteria. The same concentration was valid for the of essential oil of P. dioica and eugenol. Only for tested Cryptococcus sp. showed sensitivity of 0.5 mg/mL to MIC90. With respect to C. ambrosioides essential oil and the main component ascaridol, the two were active only for E. coli with MIC90 of 2 mg/mL. Regarding the tested fungal strains, C. ambrosioides essential oil and monoterpene ascaridol were active for all strains tested. The MIC90 for crude oil C. ambrosioides was 0.25 mg/mL for all tested candidas, and in C. albicans theresult was positive at 0.50 mg/mL, and tested for Cryptococcus. The ascaridol showed MIC90 of 0.25 mg/mL for all the lines candidas except in C. Krusi which was 0.5 mg/mL, and in the case of Cryptococcus the MIC90 was 1 mg/mL.